Effects of selected herbicides on soil microbial populations in oil palm plantation of Malaysia: a microcosm experiment - Mohd Zain, Nur Masirah; Mohamad, Rosli; Sijam, Kamaruzaman; Morshed, Md. Mahbub; Awang, Yahya (Academic Journals, 2013)
Herbicides are commonly used in Malaysia to control weeds in oil palm plantation. In addition to their impact on weeds, these herbicides are also affecting soil microorganisms which are responsible for numerous biological processes essential for crop production. In the present study, we assessed the impact of four commonly used herbicides (paraquat, glyphosate, glufosinate-ammonium and metsulfuron-methyl) on soil microbial populations in oil palm plantation. Our study showed that the herbicide treatments significantly inhibited the development of microbial populations in the soil, and the degree of inhibition closely related to the rates of their applications and varied with the types of herbicide. Paraquat caused the highest inhibitory effect to bacteria and actinomycetes, whereas fungi were most affected by glyphosate. Metsulfuron-methyl had least inhibitory effects to all the microbial populations. The highest inhibition (59.3%) for fungal population was observed at 6 DAT (days after treatment), whereas for the bacteria and actinomycetes (82.0 and 70.6%, respectively) were at 4 DAT. Increasing trend of inhibition on growth of microbial populations was observed from the initial effect until 6 DAT, followed by a drastic decrease of the inhibition at 10 DAT. No inhibition was observed at 20 DAT. The study suggests that the herbicide application to soil of oil palm plantation cause transient impacts on microbial population growth, when applied at recommended or even as high as double (2x) of the recommended field application rate.